TOTAL BAKTERI ASAM LAKTAT,PH, DAN TOTAL ASAM DADIH SUSU SAPI DENGAN PENAMBAHAN SIROP UMBI YAKON UNTUK DMT2 TAHUN 2022 - Dera Nurul Fadila, (2022)
Type 2 Diabetes mellitus (T2DM) is a type of diabetes with the most suffering in the world, thus initiating the development of functional foods to maintain glycemic control. The purpose of this study was to formulate a cow's milk dadih with the addition of yakon tuber syrup as an antidiabetic substance for people with T2DM. In addition, the specific objectives of this study were to analyze total lactic acid bacteria (LAB), pH, total acid, and organoleptic of cow's milk dadih with the addition of yacon tuber syrup. The research method used a single-factor completely randomized design (CRD) with three repetitions. Data analyses used for total LAB, pH, and total acid were One Way Anova and continued with Duncans Multiple Range Test (DMRT), while organoleptic test used Kruskal Wallis test and continued with the Mann Whitney test. The selected formula was determined using the exponential comparison method (MPE) by considering several parameters. The results of the analysis showed that the addition of yacon tuber syrup affected the pH value (p=0.016). While, it did not show a significant effect (p>0.05) on total LAB, total acid, and organoleptic. The formula chosen is product F2 with the addition of 20% yacon tuber syrup.